STUDI INTERAKSI ION LOGAM Mn2+ DENGAN SELULOSA DARI SERBUK KAYU - Risfidian Mohadi; Adi Saputra; Nurlisa Hidayati; Aldes Lesbani (Jurnal Kimia (Journal of Chemistry), 2014)
Separation of cellulose from sawdust using methanol and hydrocloric acid in various acid concentrations has been carried out. Cellulose from sawdust was characterized using FT-IR Spectroscopy and XRD difractometer. The cellulose was used as adsorbent for Mn2+ and Co2+ metal ions in aqueous medium. Adsorptions process was studied through variation of time interaction, concentration and separation desorption. FT-IR Spectrum shows that cellulose with 5% acid concentration has similarity with FT-IR cellulose standard. The XRD difractometer pattern of cellulose shows that cellulose has amorf structure. The adsorption rate constant of Mn2+ on cellulose from sawdust shows adsorption rate constant in cellulose is higher than in sawdust. Adsorption energy of Mn2+ metal ion in cellulose from sawdust was about 26.21 kJ/mol. The adsorption capacity of Mn2+ in cellulose is higher than in sawdust. The desorption of Mn2+ metal ion using H2O, Na-EDTA, Amonium acetic, and HCl shows that the adsorption mechanism of Mn2+ on cellulose and sawdust is dominated by chemical interaction.